Jati Diri Kaum Awam Dan Panggilannya Di Tengah Dunia Dewasa Ini - Silvester Manca (Jurnal Alternatif Wacana Ilmiah Interkultural, 2018)
The Vatikan Council II has returned the Church is essence as a believer community. Thus, the Church is not longer identify the clergy, but include of the laity. The laity are recognized their dignity as a member of the Church with their distinctive roles anda functions in the world order. The laity are called to the direct world order on Christ. The task can only be realized if the laity undertand the contex of the realization call properly and correctly. The first, the laity must be recognized the sign of age. It means that, the laity have to have sense of sensitvity. They are also must be in networking each other. Finally, they must be know and holdfirm fundamental principles of Christianity.